The Local Wisdom In The Practice Of Profit And Loss Sharing (PLS) In The Fishery System: A Study Of Islamic Economic Activities In Tapak Kuda Village, District of Tanjung Pura, Langkat Regency, North Sumatera Province - Muhammad Ridwan; sugianto sugianto (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2015)
This research examines the practice of profit and loss sharing (PLS) in fishery system in Tapak Kuda village of Tanjung Pura, District of Langkat. This system is implemented by the fishermen and involved many parties. This kind of profit and loss sharing system has been a local wisdom of the community of this village. This reseach finds that this type of local wisdom is a result of internalization process in the context of social construction since long time ago. This internalization involved many factors. For further study, this research recommends a deeper study on local wisdom related to Islamic economic activity of Indonesian society.